Antioxidant, antimicrobial and anticancer properties in different plant parts of Dendrobium crumenatum Sw. - Johari, Suria (2019)
Dendrobium crumenatum is commonly known as Pigeon Orchid or Orkid Merpati. There is limited information on the phytochemical properties of D. crumenatum available at present. With the great development in herbal and pharmaceutical industry, more valuable extracts are required to discover their potential. The objectives of this study were to evaluate the level of antioxidant activity as well as anticancer and antimicrobial activities in different plant parts of D. crumenatum by using different plant parts, extracting solvent, drying temperature of plant materials and shaking duration, the optimum antioxidant, antimicrobial and anticancer activity of D. crumenatum were determined. The extracts of all tested plant parts with different extracting solvents shows antioxidant activities ranging from 2.3 to 10.3 mg TE/g DW. The highest total antioxidant in for DPPH and FRAP method was found on seven days shaking duration with the value 14.41 mg TE/g DW (pseudobulb dried at 70°C) and 35.51 mg TE/g DW (stem dried at 45°C) respectively. The antimicrobial activity shows significant differences on antimicrobial activity to that of the standard antibiotic against all tested microorganisms with MIC value in range of 0.31 to 10.0 mg/ml. From the in vitro cytotoxic bioassay results, the methanolic stem extracts of D. crumenatum demonstrated moderate activities against the NCI-H460 (IC50 value of 64 μg/ml) and MCF-7 (IC50 value of 77 μg/ml).The results from this bioactivity investigation suggested that pseudobulb and stem of D. Crumenatum may have great potential for further development as cancer chemoprevention agents specifically against NCI-H460 and MCF-7 or food supplements for promoting human health.